Will the use of anabolic androgenic steroids become a significant cardiovascular risk factor in the future? - Piotr Pawłucki; Anna Maciak; Ewelina Andrasz; Paulina Cuper; Michał Sekuła; Błażej Dziurowicz (Journal of Education, Health and Sport, 2023)
Introduction and purpose: Cardiovascular diseases are the leading cause of mortality in many European countries. Major modifiable risk factors include dyslipidemia, hypertension, smoking and diabetes. The aim of our study is to draw attention to the possible impact of the use of anabolic androgenic steroids on increased cardiovascular risk.